Analisis Makna Semantik Terjemahan Lirik Lagu Dalam Single Album River Dan Kimi Wa Melody JKT48 - Masiruw, Eunique Karen; Alfarisy, Fitri (KIRYOKU, 2024)
This research aims to analyse semantic meaning from translated songs lyrics at JKT48's RIVER single album and kimi wa melody single album. In the seven translated lyrics from Japanese into indonesian in the JKT48's RIVER single album that include 4 songs Sakura no Shiori (Pembatas buku sakura), Mirai no kajitsu (Buah masa depan), and kimi ni au tabi koi wo suru (Jatuh cinta setiap bertemu dengan mu) and Kimi wa melody single album that include 3 songs Kimi wa melody (Dirimu melody), Koko ni ita koto (Kita pernah disini), and Omoide no hotondo (Sebagian besar kenangan) this research aims to describe and make classification of lexical, grammatical, and contextual meanings and also referential and non-referential meanings. The author limits this research by taking 2 categories from chaer (2014) theory including lexical, grammatical, and contextual meanings and also referential and non-referential meanings to understand more deeply the words of the lyrics than before. This research uses descriptive qualitative method where the data collected are data in the form of words and sentences by looking at the differences in meaning included in the characteristics according to Chaer (2014) including namely lexical, grammatical, and contextual meanings and also referential and non-referential meanings that exist in two song lyrics between Japanese and Indonesian translation version of JKT48's lyrics. This research is expected to provide further explanation of songs that are often heard by the wider community. Based on chaer (2014) theory, grammatical meanings be the least meaning found in all seven songs.